Boundedness of Solutions of Dirichlet Problem for a Class of Nonlinear Elliptic Equations with Weights - Cianci, Paolo (Applicable analysis, 2003)
In this article, under some Hypotheses on weights and on coefficients, using a modification of Moser's method, we establish the boundedness of solutions of Dirichlet Problem for a class of nonlinear elliptic equations.